Effect of Cross-Linking Agent on Mechanical and Permeation Properties of Criolla Orange Pectin - Garcia, Maria Guadalupe (2022)
Pectin from orange peel was extracted and cross-linked, applying different cross-linking agents to visualize any effect on its mechanical and permeation properties. Calcium chloride (II) and iron chloride (III) were the cross-linking agents. Besides, commercial pectin was also used to compare its properties with neat orange pectin. Tensile testing showed mechanical stiffness of the orange pectin matrix in the presence of cross-linking agents. Calcium ions better cross-linked the polymer matrix as shown by their highest tensile strength and elastic modulus, with moderate elongation at break. Iron ions showed a weaker cross-linking effect on the pectin matrix, improving the elastic modulus but retaining almost the same tension strength. Lower elongation at break concerning neat orange pectin was observed for cross-linked samples. Water uptake (WU) and water vapor permeation (WVP) of cross-linked samples had lower values than those of neat orange pectin. However, these results are still high compared with synthetic polymers. Finally, gas permeation assays were performed using N2, O2 and CO2 gases, according to exchangeable gases in fresh fruits and vegetable packaging. Results showed a conveniently modified atmosphere effect by avoiding CO2 permeation and stabilizing N2 and O2 selectivity.